The clinical efficacy of fluticasone propionate combined with ACEI/ARB in the treatment of immunoglobulin A nephropathy - Liping Sun; Xinyi Zi; Zhen Wang; Xinzhou Zhang (BMC Nephrology, 2023)
Abstract Background Immunoglobulin A nephropathy (IgAN) is the most common primary glomerulopathy worldwide, and lacks the effective treatment. The study was aimed to investigate the clinical efficacy of fluticasone propionate aerosol combined with angiotensin converting enzyme inhibitor / angiotensin receptor blocker (ACEI/ARB) in the treatment of IgAN. Methods 142 patients with biopsy-proven IgAN at Shenzhen People?s hospital from June 2018 to June 2020 were enrolled. The patients were randomly divided into the supportive care plus fluticasone group and the supportive care group. The patients of the supportive care plus fluticasone group were treated with fluticasone propionate aerosol (250 ?g Bid) combined with ACEI/ARB, while the supportive care group was merely treated with ACEI/ARB. The patients were followed up at 3, 6 and 9 months after enrollment. Primary outcomes include changes in proteinuria and estimated glomerular filtration rate (eGFR). Results The level of proteinuria in the supportive care plus fluticasone group was significantly lower compared with the supportive care group at 0, 3, 6 and 9 months. Meanwhile, during the follow-up period, no serious adverse events were recorded during the study in either group. However, fluticasone treatment did not alleviate the decline in eGFR. Conclusion Fluticasone propionate aerosol combined with ACEI/ARB can reduce the level of proteinuria in thetreatment of IgAN, and has no significant effects on renal function.